Analisis Keuntungan Usaha Dapur Aisyah Kelurahan Kleak Kecamatan Malalayang Kota Manado - Tongkodu, Ingrid Kezia; Tambas, Jane Sulinda; Sondakh, Mex Frans Lodwyk (AGRI-SOSIOEKONOMI, 2024)
This study aims to see how much profit Aisyah's Kitchen business in Kleak Village, Malalayang District, Manado City. The research method used is the survey method. The data required is primary data taken using questionnaires and interviews directly with business owners. The data collected will be tabulated and analyzed. The analytical tools used are profit analysis and R/C Ratio. The results showed that the profit from Aisyah's Kitchen business through the value of the R/C Ratio was 2.24 with the provisions greater than> 0 the business was declared profitable and worth developing. The results of this study can see how much profit per product, see the price per product, so that it can be seen whether it is profitable or not.